Coordination and Redox Dual‐Responsive Mesoporous Organosilica Nanoparticles Amplify Immunogenic Cell Death for Cancer Chemoimmunotherapy. Issue 26 (3rd June 2021) - Zhang, Fan; Chen, Fangman; Yang, Chao; Wang, Lei; Hu, Hanze; Li, Xuezhao; Zheng, Xiao; Wang, Zheng; Chang, Zhimin; Li, Tianyu; Li, Li; Ge, Mingfeng; et al.
Abstract: Amplifying the chemotherapy‐driven immunogenic cell death (ICD) for efficient and safe cancer chemoimmunotherapy remains a challenge. Here, a potential ICD nanoamplifier containing diselenide‐bridged mesoporous organosilica nanoparticles (MONs) and chemotherapeutic ruthenium compound (KP1339) to achieve cancer chemoimmunotherapy is tailored. KP1339‐loaded MONs show controlled drug release profiles via glutathione (GSH)‐responsive competitive coordination and matrix degradation. High concentration of MONs selectively evoked reactive oxygen species production, GSH depletion, and endoplasmic reticulum stress in cancer cells, thus amplifying the ICD of KP1339 and boosting robust antitumor immunological responses. After the combination of PD‐L1 checkpoint blockade, cancer cell membrane‐cloaked KP1339‐loaded MONs not only regress primary tumor growth with low systemic toxicity, but also inhibit distant tumor growth and pulmonary metastasis of breast cancer. The results have shown the potential of coordination and redox dual‐responsive MONs boosting amplified ICD for cancer chemoimmunotherapy. Abstract : Diselenide‐bridged mesoporous organosilica nanoparticles are selected for coordination and redox dual‐responsive delivery of the chemotherapeutic ruthenium compound KP1339. The cancer cell membrane‐cloaked immunogenic cell death nano‐amplifier performs robust suppression on primary and distant tumor growth, as well as pulmonary metastasis of breast cancer with low systematic toxicity when combined with anti‐PD‐L1.